Higgs Boson: The Ultimate Particle of the Universe - Dahal, Kul Prasad (Himalayan Physics, 2012)
The concept of basic constituent particles of matter have been changing from ancient time to present. Scientists have been looking for the Higgs since the long with experiments at CERN and Fermilab. Confirming the existence of the Higgs would only be the start of a new era of particle physics. To find the particle and characterize it, scientists are smashing beams of proton together inside LHC at close to the speed of light. The recent discovery declared that the finding is very close to the ultimate particle called Higgs particle. This is believed to be the basic building block of the universe. The Himalayan Physics Vol. 3, No. 3 2012 Page : 56-59